Formation, structural and optical characterization of neodymium doped-zinc soda lime silica based glass - Mohd Ismail, Zamratul Maisarah; Abdul Wahab, Zaidan; Matori, Khamirul Amin; Mohamed, Nurzilla; Shaari, Abdul Halim (Elsevier, 2016)
New glass system of neodymium – doped zinc soda lime silica glass has been synthesized for the first time by melt-quenching of glass waste soda lime silica (SLS) with zinc oxide (ZnO) as precursor glass and Nd2O3 as dopant. In order to examine the effect of Nd3+ on the structural and optical properties, the prepared sample of structure [(ZnO)0.5(SLS)0.5](Nd2O3)x (x = 0, 1, 2, 3, 4 and 5 wt%) was characterized through X-ray diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy, UV–Vis spectroscopy (UV–Vis) and the photoluminescence (PL). XRD pattern justifies the amorphous nature of synthesized glasses. FTIR spectroscopy has been used to observe the structural evolution of ZnO4 and SiO4 groups. The UV–Vis-NIR absorption spectra reveals seven peaks centered at excitation of electron from ground state 4I9/2 to 4D3/2 + 4D5/2 (∼360 nm), 2G9/2 + 2D3/2 + 2P3/2(∼470 nm), 2K13/2 + 4G7/2 + 4G9/2 (∼523 nm), 4G5/2 + 2G7/2 (∼583 nm), 4F9/2 (∼678 nm), 4S3/2 + 4F7/2 (∼748 nm) and 4F5/2 + 2H9/2 (∼801 nm). PL spectra under the excitation of 800 nm display four emission bands centered at 531 nm, 598 nm, 637 nm and 671 nm corresponding to 4G7/2 → 4I9/2, (4G7/2 → 4I11/2, 4G5/2 → 4I9/2), (4G5/2 → 4I11/2) and (4G7/2 → 4I13/2, 4G5/2 → 4I11/2) respectively.